2017
DOI: 10.1097/aci.0000000000000335
|View full text |Cite
|
Sign up to set email alerts
|

Allergen immunotherapy: an updated review of safety

Abstract: Purpose of review Allergen immunotherapy is the only modality that can modify the immune response upon exposure to aeroallergens and venom allergens. This review will update the allergist on recent studies evaluating safety of sublingual and subcutaneous allergen immunotherapy. Recent findings Multiple clinical trials and retrospective studies have been published evaluating overall safety of these therapies. The risk of systemic reactions with subcutaneous immunotherapy remains quite low, but near-fatal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
69
2
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 28 publications
4
69
2
14
Order By: Relevance
“…Many aspects should be considered in clinical practice—an EAACI position paper listed the contraindications to AIT [ 5 ]. Moreover, a series of recommendations should carefully comply in clinical practice, as reported in many official documents [ 77 , 78 , 79 ]. If AIT is prescribed and administered correctly and prudently, AIT, mainly SLIT, is safe and well-tolerated also in children with allergic asthma.…”
Section: Safety Issuementioning
confidence: 99%
“…Many aspects should be considered in clinical practice—an EAACI position paper listed the contraindications to AIT [ 5 ]. Moreover, a series of recommendations should carefully comply in clinical practice, as reported in many official documents [ 77 , 78 , 79 ]. If AIT is prescribed and administered correctly and prudently, AIT, mainly SLIT, is safe and well-tolerated also in children with allergic asthma.…”
Section: Safety Issuementioning
confidence: 99%
“…After identification of the major risk factors (and particularly the high risk associated with uncontrolled asthma when the allergen extract is injected), the prevalence of severe reactions is very low. 61 However, in patients who develop such reactions, switching to other routes of administration (especially the safer sublingual route) or withdrawal of AIT could prevent further reactions. 62 This strategy denies the patient treatment that could modify the natural history of allergy.…”
Section: Issues To Be Investigated In Omalizumab Treatmentmentioning
confidence: 99%
“…Cochrane systematic reviews and meta-analyses have demonstrated that the frequencies of rescue medication use and clinical symptoms are reduced in patients with allergic asthma and allergic rhinitis after SLIT and SCIT. 6 SLIT had a lower incidence of systemic reactions but a higher incidence of local site reactions than SCIT and is therefore strongly recommended in the treatment of allergic rhinitis. 6 The CD4 + CD25 + Foxp3 + Treg cells induced by tolerogenic dendritic cells (DCs) in the oral mucosa mediate immune tolerance, thus improving the clinical efficacy after SLIT.…”
mentioning
confidence: 99%
“… 6 SLIT had a lower incidence of systemic reactions but a higher incidence of local site reactions than SCIT and is therefore strongly recommended in the treatment of allergic rhinitis. 6 The CD4 + CD25 + Foxp3 + Treg cells induced by tolerogenic dendritic cells (DCs) in the oral mucosa mediate immune tolerance, thus improving the clinical efficacy after SLIT. 7 SLIT has no risk of severe systemic reactions, which is considered an advantage over SCIT, because allergens are mostly captured by tolerogenic DCs before they reach the mast cells during SLIT.…”
mentioning
confidence: 99%
See 1 more Smart Citation